A review of ventilation opening area terminology - Jones, Benjamin M.; Cook, Malcolm J.; Fitzgerald, Shaun D.; Iddon, Christopher R. (Elsevier, 2016)
The design of a natural ventilation strategy requires the establishment of the location and size of a series of purpose provided ventilation openings (PPOs). The success of the design is dependent on knowledge of the aerodynamic performance of the PPOs often described by their geometry (normally an area) and resistance to airflow. The incorrect interpretation of this information can lead inappropriate ventilation strategies and buildings that overheat and have an excessive energy demand.